STUDENT EXCHANGE: CULTURAL IDENTITY OF GUIDANCE AND COUNSELING STUDENTS - Nur Asiah; Ipah Saripah (OPTIMA: Journal Of Guidance and Counseling, 2021)
The student exchange program provides opportunities for students to meet each other and recognize the culture of the foreign regions that host them in an atmosphere of tolerance and multiculturalism. This article aims to analyze the level of cultural identity possessed by Guidance and Counseling students returning from a student exchange program. This study uses a quantitative approach using a descriptive survey method. The research sample consisted of 30 Guidance and Counseling students with cultural differences who participated in student exchange programs at the National and International levels with a minimum length of stay of 6 months. The instrument used was a questionnaire about the cultural identity of origin which was adapted from The Utrecht-Management of Identity Commitments Scale (The U-MICS). The results of the study were analyzed using the average formula and the help of the SPSS program. The results showed that 63.3% of BK students' cultural identity was in the high category